Social inclusion in the digital Age: Legal aspects (Research, Society and Development, 2021)
Objective: to promote awareness among law enforcers regarding legislation that supports digital social inclusion. Method: we performed a literature review by consulting the Google Escolar database to survey the articles with the descriptors - digital inclusion legislation; social and digital inclusion. Conclusion: the digital divide, unfortunately, is still present in Brazilian society today, and in order to promote the proper inclusion of these people we need to think about education in this sense, as the citizen's first contact with the digital world.